Modified Fruit Fly Optimization Algorithm for Analysis of Large Antenna Array - Nattaset Mhudtongon; Chuwong Phongcharoenpanich; Supakit Kawdungta (My University, 2015)
This research paper deals with the optimization of a large antenna array for maximum directivity using a modified fruit fly optimization algorithm (MFOA) with random search of two groups of swarm and adaptive fruit fly swarm population size. The MFOA is utilized to determine three nonlinear mathematical test functions, analysis of the optimal number of elements and optimal element spacing of the large antenna array, and analysis of nonuniform amplitude of antenna array. The numerical results demonstrate that the MFOA is effective in solving all test function and electromagnetic problems. The advantages of the proposed algorithm are ease of implementation, large search range, less processing time, and reduced memory requirement.
Keywords: Directivity; Antenna Design and Optimization